Fundamentals of Entrepreneurship (ENT300) : S.A.V.E.D haircut. / Asrizal Hakim Othman … [et l.] - Othman, Asrizal Hakim; Collin, Davina Elvie; Angin, Evelyn Kurash; Muhidin, Saidatul Anisa; Dickie, Veronica Wilda (2019)
S.A.V.E.D Haircut is a haircut services which is providing 12-hours services. It is located at Universiti Teknologi Mara (UiTM) Campus 2, 94300 Kota Samarahan. Our motto is “smart choice, smart cutting”. In order to achieve our motto, we will plan our business thoroughly from each aspect. We plan our financial by budgeting each sector such as for materials, salaries and so on. For our business haircut, we budgeting RM159 for machinery only. Meanwhile, other materials such as shampoo, we allocated RM500 monthly for all materials needed.